Metal-embedded nitrogen-doped graphene for H2O molecule dissociation. (May 2017) - Liu, Lin-Lin; Chen, Chun-Ping; Zhao, Lu-Si; Wang, Ying; Wang, Xiao-Chun
Abstract: The H2 O molecule dissociation on the alkali-earth (Ba and Mg) or transition-metal (Ti)-embedded nitrogen-doped graphene was studied systematically using first-principles calculation. The metal-embedded nitrogen-doped graphene (MN4 -graphene) (M = Ba, Mg and Ti) membranes are good candidates for single-atom catalysts (SACs), because the single metal atom can be strongly trapped in the divacancy of the MN4 -graphene membranes and exists in the isolated form. The significant activation of the reactant H2 O molecule was observed. The binding energy of the first H atom of H2 O molecule adsorbed on the MN4 -graphene (M = Ba, Mg and Ti) membranes are 2.88 eV, 3.11 eV and 0.75 eV respectively, which are notable smaller than that 6.01 eV for free H2 O molecule. Thus, the TiN4 -graphene membrane can remarkably decrease the potential barrier of H atom dissociated from H2 O molecule, which is a very promising SAC candidate for molecular dissociator. Our report comes as a first report towards the demonstration of the MN4 -graphene membranes for the H2 O molecule dissociation. Graphical abstract: